Analysis of the Causes of Hyperinflation in The Republic of Croatia 1991-1993 - Denis Družić; Dubravka Maras (Mednarodno Inovativno Poslovanje)
The paper analyses the causes and dynamics of hyperinflation in the Republic of Croatia – which lasted from 1991 to 1993. Through the analysis of primary and secondary sources, the individual causes of hyperinflation are broken down, and based on the analysis the authors conclude that while the primary inflationary impulse is due to the economic legacy of Yugoslavia, and historical circumstances such as war and the collapse of the former state, the rise in prices would not have been maintained had there not been inflationary taxation as a form of accumulation of foreign exchange reserves. The authors aim to provide newer generations of economists with a complete overview of factors that instigated and maintained inflation in this turbulent and transitory period in Croatia’s history.